O fenômeno do hibridismo organizacional nas organizações sem fins lucrativos : o caso da Associação Ateliê de Ideias - Senna, Rubens Patrocínio (2017)
The objective of this study is to understand how the phenomenon of organizational hybridity is materialized in the Association Atelier of Ideas, in its activities of raising funds for the development of social projects with the communities served. The Ass